PENGARUH EFFECTIVE COMMUNICATION DAN MOTIVATION TERHADAP SELF DEVELOPMENT DI LINGKUNGAN KAMPUS: Studi Pada Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Bandar Lampung - Fiqih, Muhammad Rizvy Al; Dunan, Hendri (Media Mahardhika, 2025)
As individuals who undergo education at the university level, students as the nation's successors must have a strong foundation in self-development in order to compete in the outside world, good self-development is obtained from the process of effective communication and motivation. This study was conducted to analyze whether effective communication and motivation have a major influence on self-development studies of students of the Faculty of Economics and Business, Bandar Lampung University. The type of research method applies a quantitative approach with a sampling of 73 respondents. The method used is multiple linear regression analysis. With the results stating that effective communication and motivation have a large and significant effect on self-development partially and simultaneously on students of the Faculty of Economics and Business, Bandar Lampung University.